2023
DOI: 10.1038/s41598-023-38506-x
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin and DHA supplementation ameliorates the proteomic profile of perinatal undernutrition-induced adipose tissue dysfunction in adult life

Abstract: Maternal diet is an essential factor that directly and indirectly regulates fetal growth. Exposure to certain environmental conditions substantially impacts an individual's short- and long-term health. Adipose tissue dysfunction is a worldwide chronic disease caused by improper lipid build-up in adipose tissue leading to obesity. Therefore, it is the need of the hour to invent anti-obesity agents. As a keto–carotenoid, Astaxanthin (AsX) has been shown to have preventive effects against problems associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Our previous study revealed that a 30% reduction in maternal diet during pregnancy induces stress, which leads to adipose tissue dysfunction in adult life. Treatment with AsX and DHA signi cantly improved the perinatal undernutrition-induced differential protein expression in adipose tissue [42].…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study revealed that a 30% reduction in maternal diet during pregnancy induces stress, which leads to adipose tissue dysfunction in adult life. Treatment with AsX and DHA signi cantly improved the perinatal undernutrition-induced differential protein expression in adipose tissue [42].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, transcriptomic investigations can uncover the gene networks linked with growth promotion, immune modulation, and antioxidant defense in response to astaxanthin supplementation [179,180]. Proteomic assessments can pinpoint specific proteins subject to upregulation or downregulation upon astaxanthin exposure, offering insight into the pivotal functional contributors involved in the observed effects [181]. Metabolomic profiling can divulge insights into the metabolic shifts prompted by astaxanthin and unearth potential indicators of its advantageous outcomes [182].…”
Section: Future Directions and Research Gapsmentioning
confidence: 99%